2015
DOI: 10.1017/s1366728915000863
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and input in bilingual development

Abstract: A growing literature on bilingual development explores relationships between language exposure and learning outcomes. Vocabulary size and pace of grammar learning have been claimed to be causally related to amounts or types of exposure to each language. Strong claims are made about the role of exposure on bilingual outcomes. Some researchers posit a unique learning result: a ‘weak language’. In a critical review, I voice reasons for scepticism that quantity or quality of exposure alone will explain findings. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 87 publications
3
63
0
1
Order By: Relevance
“…The bilingual language experience is, by its very nature, distributed across language, andat least in relative termsbilingual children receive proportionally less input in each language that monolingual children. Although relative amount of exposure is only an indirect and imperfect approximation of input quantity (Carroll, 2017;De Houwer, 2014;Hurtado, Grüter, Marchman & Fernald, 2014), it has repeatedly been shown to correlate robustly with measures of language proficiency (Hoff, Welsh, Place & Ribot, 2014;Unsworth, 2013).…”
Section: The Role Of Language Experience Language Proficiency and Sesmentioning
confidence: 99%
“…The bilingual language experience is, by its very nature, distributed across language, andat least in relative termsbilingual children receive proportionally less input in each language that monolingual children. Although relative amount of exposure is only an indirect and imperfect approximation of input quantity (Carroll, 2017;De Houwer, 2014;Hurtado, Grüter, Marchman & Fernald, 2014), it has repeatedly been shown to correlate robustly with measures of language proficiency (Hoff, Welsh, Place & Ribot, 2014;Unsworth, 2013).…”
Section: The Role Of Language Experience Language Proficiency and Sesmentioning
confidence: 99%
“…Parent reports, which have been frequently used in previous research to measure language input, are a feasible method to examine the dual language exposure of simultaneous and sequential bilinguals (Paradis, 2017) despite its limitations in measurement precision (Carroll, 2017). Studies that used parent reports have shown that there is variability in bilingual language use among Spanish-speaking families living in the United States.…”
Section: Sequential Bilingual Children's Exposure To L1 and L2 At Homementioning
confidence: 99%
“…Clearly, features such as proficiency, current usage, history of acquisition and social context may shift over the lifespan and be more or less relevant to report for child and adult participants. For example, while sufficient proficiency in multiple languages is often a primary criterion for bilingualism, determining which skills to measure or where to set the bar is a complex question (Carroll, 2017). In fact, it may not be realistic to assume bilinguals can attain proficiency comparable to that of monolinguals (Grosjean, 1989).…”
Section: Introductionmentioning
confidence: 99%